Decadal-Scale Acidification Trends in Adjacent North Carolina Estuaries: Competing Role of Anthropogenic CO2 and Riverine Alkalinity Loads - Van Dam, Bryce R.; Wang, Hongjie (Frontiers in Marine Science, 2019)
Decadal-scale pH trends for the open ocean are largely monotonic and controlled by anthropogenic CO2 invasion. In estuaries, though, such long-term pH trends are often obscured by a variety of other factors, including changes in net metabolism, temperature, estuarine mixing, and riverine hydrogeochemistry. In this study, we mine an extensive biogeochemical database in two North Carolina estuaries, the Neuse River estuary (NeuseRE) and New River estuary (NewRE), in an effort to deconvolute decadal-scale trends in pH and associated processes. By applying a Generalized Additive Mixed Model (GAMM), we show that temporal changes in NewRE pH were insignificant, while pH decreased significantly throughout much of the NeuseRE. In both estuaries, variations in pH were accompanied by increasing river discharge, and were independent of rising temperature. Decreases in bottom-water pH in the NeuseRE coincided with elevated primary production in surface waters, highlighting the importance of eutrophication on long-term acidification trends. Next, we used a simple mixing model to illustrate the impact of changing river discharge on estuarine carbonate chemistry. We found that increased riverine alkalinity loads to the NewRE likely buffered the impact of CO2-intrusion-induced acidification. In the NeuseRE, however, elevated dissolved inorganic carbon loads further decreased the buffering capacity, exacerbating the effects of CO2-intrusion-driven acidification. Taken together, the findings of this study show that future trajectories in estuarine pH will be shaped by complex interactions among global-scale changes in climate, regional-scale changes in precipitation patterns, and local-scale changes in estuarine biogeochemistry.